Benefits of conventional anterior codend meshes turned 90° in an Australian trawl fishery are limited to an improved quality of Neoplatycephalus conatus - Broadhurst, Matt K.; Knuckey, Ian A.; Millar, Russell B. (Frontiers in Marine Science, 2022)
Turning conventional diamond-shaped meshes 90° (‘T90’) in trawl extensions or codends is a simple modification for consistently increasing lateral openings and has improved size selection in several European fisheries. Here we investigate the effects of an industry-instigated cylinder of T90 meshes in the anterior codend of a trawl fished in the Great Australian Bight. Compared to the traditional codend ( 5.4 m long) comprising a 93.5-mm stretched mesh opening (SMO) and double 4.1-mm-diameter twine throughout, the new T90 configuration comprising 3 m of the same mesh turned 90° in the anterior section did not significantly affect catches of any discarded or retained species, or sizes of the primary target, deepwater flathead, Neoplatycephalus conatus. The only significant impact of T90 was a slightly improved quality of deepwater flathead (determined by the ‘quality index method’), attributed to some release of abrasive debris from the codend. The absence of any effects of the T90 mesh on selection might reflect the small mesh size relative to most key species and the thick twine which probably negated some of the anticipated increases in lateral mesh openings. The results reiterate the need to match the mesh perimeter to the sizes of the key target prior to efforts at maximising lateral openings (via various established technical options), but nevertheless imply the benefits of T90 mesh may extend beyond selection.